Knowledge and competitive advantage, the coevolution of firms, technology and national institutions - Lenway, Stefanie Ann; Murtha, Thomas P (Journal of International Business Studies, 2004)
This issue of JIBS offers reviews of two books that analyse the dynamic interaction between the business environments and business strategies in very different ways. The institutional underpinnings for business strategies are a major research topic for comparative management, aiming to explain why in different contexts firms pursue different strategies, and with different implications for performance. J Peter Murman in ‘Knowledge and Competitive Advantage’ takes a historical perspective focusing on the co-evolutionary processes between national innovation systems, business strategies, and performance. This books thus adds to the industry-level longitudinal research reviewed in JIBS no. 4/2003, Tom Murtha et al.'s ‘Managing New Industry Creation’ and David McKendrick et al.'s ‘From Silicon Valley to Singapore’.